Bibliography of the Works of Rev. Dr. Hab. Andrzej Bruździński, Professor of PUJPII - Bartłomiej Wołyniec (Folia Historica Cracoviensia, 2020)
Bibliography of the Works of Rev. Dr. Hab. Andrzej Bruździński, Professor of PUJPII